Incomplete information, credibility and the Core - Bhaskar Dutta; Rajiv Vohra (Brown University, Department of Economics, 2001)
An appropriate (interim) notion of the core for an economy with incomplete information depends on the amount of information that coalitions can share. The coarse and fine core, as originally defined by Wilson (1978), correspond to two polar cases, involving no information sharing and arbitrary information sharing, respectively. We propose a newcore notion, the credible core, which incorporates incentive compatibility constraints, and is based on the idea that a coalition can coordinate its potential objection to a status-quo over an event that can be credibly inferred from the nature of the objection being contemplated.
Keywords: C71; D82; D51; 330; Core; Asymmetric Information; Incentive Compatibility; Credibility; Durability; Core; Unvollkommene Information; Asymmetrische Information; Glaubwürdigkeit; Theorie